PENGARUH SUBSTITUSI RUMPUT LAUT (EUCHEUMA COTTONII) DAN JAMUR TIRAM (PLEUROTUS OSTREATUS) TERHADAP DAYA TERIMA DAN KANDUNGAN SERAT PADA BISKUIT - Cindhy Pamela Kesuma; Annis Catur Adi; Lailatul Muniroh (Media Gizi Indonesia, 2015)
Biscuit is a food product made from the basic ingredient ﬂ our that baked until moisture content less than 5%.  Commercial biscuits are generally rich in energy and high in sugars derive from carbohydrates and fats, but low inﬁ ber. Seaweed (Eucheuma cottonii) and arrowroot ﬂ our are high-ﬁ ber food, while oyster mushroom contains high protein so it can be a potential ingredients to be substituted in biscuits. The addition of seaweed and oyster mushroom was expected to increase the ﬁ ber content of biscuits compared to other biscuits. This study aimed to determine the acceptability and improve ﬁ ber content in biscuits with the substitution of seaweed and oyster mushrooms. This study used a completely randomized design (CRD) with 3 treatments and 4 repetitions. Arrowroot ﬂ our substitution treatment,seaweed, and oyster mushrooms were applied as F1 (25%: 50% to 25%), F2 (25%: 45%: 30%), and F3 (25%: 40%: 35%). Acceptability of biscuits based on organoleptic test and ﬁ ber content from calculation based on Indonesia Food Composition Database and also laboratory analysis using proximate test. This research showed that formula 3 had the highest score based on organoleptic test with score 2.86. The highest ﬁ ber content per serving (50 g) was found in formula 1 with 10.59 g of ﬁ ber. The conclusion of this research is that the biscuit with substitution of seaweed andoyster mushroom has a good acceptability and higher ﬁ ber content compared to commercial biscuits.Keywords: biscuit, oyster mushroom (Pleurotus ostreatus), seaweed (Eucheuma cottonii)